2015
DOI: 10.1007/s11010-015-2436-9
|View full text |Cite
|
Sign up to set email alerts
|

C-phycocyanin prevents cisplatin-induced mitochondrial dysfunction and oxidative stress

Abstract: The potential of C-phycocyanin (C-PC) to prevent cisplatin (CP)-induced kidney mitochondrial dysfunction was determined in CD-1 male mice. The CP-induced mitochondrial dysfunction was characterized by ultrastructural abnormalities and by decrease in the following parameters in isolated kidney mitochondria: adenosine diphosphate (ADP)-induced oxygen consumption (state 3), respiratory control ratio, ADP/oxygen (ADP/O) ratio, adenosine triphosphate synthesis, membrane potential, calcium retention, glutathione (GS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 65 publications
3
18
0
Order By: Relevance
“…As mentioned earlier, oxidative stress damage is involved in the mechanisms of cisplatin‐induced nephrotoxicity 25 . The results of present study showed that the depletion of GSH along with an increase of MDA levels in HEK‐293 cells happened when exposed to cisplatin compared to the normal group ( P < .01 and P < .05).…”
Section: Resultssupporting
confidence: 64%
“…As mentioned earlier, oxidative stress damage is involved in the mechanisms of cisplatin‐induced nephrotoxicity 25 . The results of present study showed that the depletion of GSH along with an increase of MDA levels in HEK‐293 cells happened when exposed to cisplatin compared to the normal group ( P < .01 and P < .05).…”
Section: Resultssupporting
confidence: 64%
“…As previously described, oxidative stress injury participated in the mechanisms of cisplatin-induced AKI [ 32 ]. As indicated in Figure 2 , cisplatin treatment caused conspicuous reduction of glutathione (GSH) level and superoxide dismutase (SOD) activity accompanied by increase of MDA content, compared with control group ( p < 0.05 or p < 0.01).…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned earlier, oxidative stress damage is involved in the mechanisms of cisplatin-induced nephrotoxicity [ 34 ]. As shown in Figure 3 , cisplatin exposure resulted in dramatic decrease of GSH content and SOD activity along with increase of MDA, compared to the normal group ( p < 0.01).…”
Section: Resultsmentioning
confidence: 99%